Integrin α2β1 Expression Regulates Matrix Metalloproteinase-1-Dependent Bronchial Epithelial Repair in Pulmonary Tuberculosis - Brilha, Sara; Chong, Deborah L. W.; Khawaja, Akif A.; Ong, Catherine W. M.; Guppy, Naomi J.; Porter, Joanna C.; Friedland, Jon S. (Frontiers in Immunology, 2018)
Pulmonary tuberculosis is caused by inhalation of Mycobacterium tuberculosis, which damages the bronchial epithelial barrier to establish local infection. Matrix metalloproteinase -1 plays a crucial role in the immunopathology of tuberculosis, causing breakdown of type I collagen and cavitation, but this collagenase is also potentially involved in bronchial epithelial repair. We hypothesized that the extracellular matrix modulates Mycobacterium tuberculosis driven matrix metalloproteinase-1 expression by human bronchial epithelial cells, regulating respiratory epithelial cell migration and repair. Medium from monocytes stimulated with Mycobacterium tuberculosis induced collagenase activity in bronchial epithelial cells, which was reduced by ~87% when cells were cultured on a type I collagen matrix. Matrix metalloproteinase-1 had a focal localization, which is consistent with cell migration, and overall secretion decreased by 32% on type I collagen. There were no associated changes in the specific tissue inhibitors of metalloproteinases. Decreased matrix metalloproteinase-1 secretion was due to ligand-binding to the α2β1 integrin and was dependent on the actin cytoskeleton. In lung biopsies samples from patients with pulmonary tuberculosis, integrin α2β1 is highly expressed on the bronchial epithelium. Areas of lung with disrupted collagen matrix showed an increase in MMP-1 expression compared with areas where collagen was comparable to control lung. Type I collagen matrix increased respiratory epithelial cell migration in a wound-healing assay and this too was matrix metalloproteinase-dependent, since it was blocked by the matrix metalloproteinase inhibitor GM6001. In summary, we report a novel mechanism by which α2β1-mediated signals from the extracellular matrix modulate matrix metalloproteinase-1 secretion by human bronchial epithelial cells, regulating their migration and epithelial repair in tuberculosis.